1986
DOI: 10.1123/jsp.8.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Physical Activity in Sedentary Women: Information, Locus of Control, and Attitudes

Abstract: This study assessed the efficacy of counseling sessions compared to a waitlist group on initiation of a physically active lifestyle. Sedentary women were randomly assigned to 1-hour counseling interviews or to a waitlist control. Subjects were administered the Exercise Locus of Control scales (McCready, 1984), the Revised Children's Attitude Toward Physical Activity inventory (Schutz, Smoll, & Wood, 1981a), a 7-day exercise history, activity satisfaction scales, and goal success scales. One month later the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
9
0
6

Year Published

1988
1988
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
3
9
0
6
Order By: Relevance
“…IEXLOC was significantly and positively correlated with powerful others EXLOC (POEXLOC) (r =.44, P < .001) and chanceEXLOC (CEXLOC) (r=.40,p <.001), whilePOEXLOC and CEXLOC were also highly correlated (r =.64,p<.001).The original validation work reported negative correlations between IEXLOC with POEXLOC (-.14) and CEXLOC (-.40), while CEXLOC and POEXLOC were weakly related (.40). In addition, while the distribution ofIEXLOC in our sample (M = 26.6, SD = 3.1) was comparable to those reportedin the EXLOC validation studies (McCready & Long, 1985;Long & Haney, 1986) (Wallston & Wallston, 1981), it appears the EXLOC scales are not valid for college students. The measures of supervised (Long & Haney, 1986) and free-living (McCready & Long, 1985) activity employed in the scales' construct validation work were not standardized or validated with the samples tested, and this fact also obscures the validation workreported for the scales.…”
supporting
confidence: 46%
See 2 more Smart Citations
“…IEXLOC was significantly and positively correlated with powerful others EXLOC (POEXLOC) (r =.44, P < .001) and chanceEXLOC (CEXLOC) (r=.40,p <.001), whilePOEXLOC and CEXLOC were also highly correlated (r =.64,p<.001).The original validation work reported negative correlations between IEXLOC with POEXLOC (-.14) and CEXLOC (-.40), while CEXLOC and POEXLOC were weakly related (.40). In addition, while the distribution ofIEXLOC in our sample (M = 26.6, SD = 3.1) was comparable to those reportedin the EXLOC validation studies (McCready & Long, 1985;Long & Haney, 1986) (Wallston & Wallston, 1981), it appears the EXLOC scales are not valid for college students. The measures of supervised (Long & Haney, 1986) and free-living (McCready & Long, 1985) activity employed in the scales' construct validation work were not standardized or validated with the samples tested, and this fact also obscures the validation workreported for the scales.…”
supporting
confidence: 46%
“…In addition, while the distribution ofIEXLOC in our sample (M = 26.6, SD = 3.1) was comparable to those reportedin the EXLOC validation studies (McCready & Long, 1985;Long & Haney, 1986) (Wallston & Wallston, 1981), it appears the EXLOC scales are not valid for college students. The measures of supervised (Long & Haney, 1986) and free-living (McCready & Long, 1985) activity employed in the scales' construct validation work were not standardized or validated with the samples tested, and this fact also obscures the validation workreported for the scales. Moreover, evidence for the predictivevalidity oftheEXLOC scales has not been published, and it is noteworthy that in an early validation study (McCready & Long, 1985) general locus of control was shown to be a better predictor of supervised exercise than was EXLOC; both were weak predictors, however.…”
supporting
confidence: 46%
See 1 more Smart Citation
“…Long and Haney (1986) found that 'counselling interviews' undertaken by a trained counsellor initiated an active lifestyle in previously sedentary women compared to a control group. Harris and colleagues (1989) acknowledged that whilst there was little objective evidence for the effectiveness of physical activity counselling by primary care physicians, preliminary data did reveal that a positive effect could be achieved, and that this form of counselling should be routine in the setting of clinical practice.…”
Section: Exercise Consultationmentioning
confidence: 95%
“…An exercise consultation session allows clients to discuss and explore issues relating to: current physical activity habits, physical activity history, barriers to change, support structures, knowledge of facilities, opportunities and goal setting. Despite the limited amount of evidence to support its application, the practice of exercise consultation has been advocated by leading researchers and organisations (Loughlan and Mutrie 1996, Miller and Rollnick 1991, Long and Haney 1986 Taylor et al1989, Centre for Disease Control [CDC] 1993). The ACSM and CDC issued a joint statement which advised doctors and other health professionals to "develop effective ways to teach physical activity counselling and incorporate them into the curricula for health professionals" (Scottish Needs Assessment Programme 1996 ).…”
Section: Exercise Consultationmentioning
confidence: 99%